PENGARUH PENERAPAN STRATEGI PEMBELAJARAN GUIDED NOTE TAKING (GNT) DENGAN MENGOPTIMALKAN PENGGUNAAN ALAT PERAGA TERHADAP HASIL BELAJAR BIOLOGI SISWA SMA NEGERI KEBAKKRAMAT TAHUN PELAJARAN 2011/2012 - Sulistyaningrum, Dyah Erlina; Santosa, Slamet; Ariyanto, Joko (Pendidikan Biologi, 2012)
ABSTRACT ? This research is aimed to  know effect  of implementation  strategy Guided Note Taking (GNT)  with optimalized learning  equipment  towards  biology  learning achievement. This research held upon senior high school student of SMA kebakkramat in academic year 2011/2012. Guided Note Taking (GNT)  with optimalized  learning  equipment  was expected to be more effective rather than if use convensional method. All student of SMA Kebakkramat had been chosen as a research population. Since, not all student was not attending biological class, hence, randomly, 2 clusters were selected representing the control class (for where the experimental treatment was not carried out) and the experimental class for where the  Guided Note Taking (GNT)  with optimalized learning equipment was applied upon. Quasy-experimental method was designed to achieve the stated research objectives following the quantitative paradigm used in this research. In addition, Randomized Subjects Posstest Only Control Group Design  was used as a research design to facilitate the data collection procedures. The data were collected using several techniques namely, questionnaire,  posttest with multiple choice, observation tools and related document. The final obtained data were then analyzed using t- test method. The results of this research showed that the implementation of the strategy has significantly affected the  biology  learning achievement.  It has been proven to have an impact towards cognitive, affective and psychomotor aspects. Keywords: Guided Note Taking (GNT), Learning Equipment, Biology Learning Achievement